2013
DOI: 10.1016/j.jcis.2013.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced displacement of a liquid pushed by a viscoelastic fluid

Abstract: We consider the displacement, in a rectangular channel, of a Newtonian oil pushed by different types of liquids (Newtonian, shear-thinning, viscoelastic) of slightly higher apparent viscosity. In the absence of viscoelastic effects the interface between the two fluids becomes sharper at larger velocities, so that the thickness of the lateral film left behind increases with the flow rate. On the contrary, with a viscoelastic fluid, the shape of the interface is almost independent of the velocity so that the thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 26 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Our recent simulations of viscoelastic flow through symmetric and asymmetric set of cylinders and through a random porous medium show that the origin of these instabilities are more related to the viscoelastic shear stress than to extensional contributions [25,43]. Recent findings by Clarke et al [18] , Avendano et al [44] and Nilsson et al [45] show the possible effects of viscoelasticity in enhanced displacement. Rodriguez de Castro et al [46] very recently showed effects of shear thinning fluids on residual oil formation.…”
Section: Introductionmentioning
confidence: 62%
“…Our recent simulations of viscoelastic flow through symmetric and asymmetric set of cylinders and through a random porous medium show that the origin of these instabilities are more related to the viscoelastic shear stress than to extensional contributions [25,43]. Recent findings by Clarke et al [18] , Avendano et al [44] and Nilsson et al [45] show the possible effects of viscoelasticity in enhanced displacement. Rodriguez de Castro et al [46] very recently showed effects of shear thinning fluids on residual oil formation.…”
Section: Introductionmentioning
confidence: 62%
“…Several proposed mechanisms rely on a potential influence of polymers on the immiscible fluid interface. For example, it has been speculated that polymer solution viscoelasticity alters the shape of the fluid displacement front in a porous medium . However, how this process impacts macroscopic fluid recovery is unclear.…”
Section: Improved Fluid Recovery From Porous Mediamentioning
confidence: 99%
“…For example, it has been speculated that polymer solution viscoelasticity alters the shape of the fluid displacement front in a porous medium. [199] However, how this process impacts macroscopic fluid recovery is unclear. In another mechanism, it is speculated that the extensional viscosity of polymer solutions suppresses nonaqueous globules from breaking up as they transit through the tortuous pore space.…”
Section: Improved Fluid Recovery From Porous Mediamentioning
confidence: 99%